Evaluation of the protective efficiency of an autogenous Vibrio anguillarum vaccine in lumpfish (Cyclopterus lumpus) under controlled and field conditions in Atlantic Canada - Onireti, Oluwatoyin B.; Cao, Trung; Vasquez, Ignacio; Chukwu-Osazuwa, Joy; Gnanagobal, Hajarooba; Hossain, Ahmed; Machimbirike, Vimbai I.; Hernandez-Reyes, Yenney; Khoury, Antoine; Khoury, Andre; O’Brien, Nicole; George, Sheldon; et al. (Frontiers in Aquaculture, 2023)
Lumpfish (Cyclopterus lumpus) have become the predominant cleaner fish species used in North American salmon aquaculture. Vibrio anguillarum is a frequent pathogen of lumpfish in Atlantic Canada, and current vaccines against local isolates conferred low to moderate efficacy. This study evaluated the safety and efficiency of a V. anguillarum autogenous vaccine under controlled and field conditions. Two safety trials were conducted following the Canadian Food Inspection Agency (CFIA) regulations before field trial testing. The first safety trial was a common garden assay, and PIT-tagged lumpfish were used for five treatments per tank (PBSnegative control, Lab vaccine-positive control, autogenous intraperitoneal (IP) vaccine, autogenous dip vaccine, autogenous dip-IP boosted vaccine) in triplicates. Weight, gross pathology, and IgM titers were evaluated to determine the vaccine's safety. After 10 weeks postvaccination (wpv), lumpfish were bath-challenged with a lethal dose (1.24 x 10 6 CFU/mL) of V. anguillarum serotype O2. Survival rate, IgM titers, memory immune response, and crossimmune protection were evaluated. The second safety trial was conducted using a double vaccine dose in two groups, PBS and autogenous IP. The gross pathology score indicated a normal immune response without tissue damage, and no mortality nor fish health issues were observed in the immunized animals. The IP route of administration conferred the highest protection against the V. anguillarum challenge. The autogenous vaccine conferred long-term immunity but did not confer cross-protection against V. anguillarum serotype O1. To evaluate the efficiency of the autogenous vaccine under field conditions, 58,976 naïve lumpfish (8-10 g) were IP immunized with either the autogenous vaccine or the commercial Forte micro IV vaccine. After 7 wpv, the lumpfish were equally distributed into eight sea cages and co-cultivated with Atlantic salmon smolts (60,000 per cage). Lumpfish IgM titers, tissue bacterial loads, mortality, and sea lice count on salmon were monitored. The autogenous vaccine and Forte vaccine confer acceptable protection to the lumpfish in sea cages. No significant difference was observed between lumpfish vaccinated with autogenous and commercial vaccines under field conditions.